Porokeratosis Ptychotropica with Penoscrotal Involvement - Raghuvir Alias Tanmay Madan Kane; Tejas Satyawan Naik; Varadraj V Pai; Pankaj Shukla (Clinical Dermatology Review)
Porokeratosis is a skin condition characterized by annular plaques with keratotic margins that histopathologically resemble a wall and cornoid lamellae. Among the various clinical variants, porokeratosis ptychotropica is an uncommon and poorly understood condition. This condition is marked by verrucous plaques that resemble psoriasis and commonly afflict the buttocks, most notably the gluteal cleft, with or without involvement of the extremities. Itching is a frequent symptom. We report a case involving the penoscrotal area.